Case report: Amnestic mild cognitive impairment in multiple domains associated with neurofascin 186 autoantibodies: Case series with follow-up and review - Hansen, Niels; Sagebiel, Anne; Rentzsch, Kristin; Hirschel, Sina; Wiltfang, Jens; Schott, Björn H.; Claudia, Bartels (Frontiers in Psychiatry, 2023)
Background: Neurofascin 186 autoantibodies are known to occur with a diseased peripheral nervous system. Recently, also additional central nervous system (CNS) involvement has been reported in conjunction with neurofascin 186 autoantibodies. Our case enlarges the spectrum of neurofascin 186 antibody-related disease to include mild cognitive impairment (MCI). Methods: We report here a case after having examined the patient files retrospectively, including diagnostics such as blood and cerebrospinal fluid (CSF) analysis involving the determination of neural autoantibodies, brain magnetic resonance imaging (MRI), brain fluorodesoxyglucose positron emission tomography (FDG-PET), and extensive neuropsychological testing. Results: We report on two patients with MCI . Brain MRI showed cerebral microangiopathy in both patients, but brain FDG-PET demonstrated pathology in the right prefrontal cortex, in the right inferior parietal cortex, and in both lateral occipital cortices in one patient. Neurofascin 186 antibodies were detected in serum in both patients, and neurofascin 186 autoantibodies were also detected in the CSF of one of these patients. At follow-up six month later, neurofascin 186 autoantibodies disappeared in one patient while persisting in the other. Conclusions: We report on two individuals presenting MCI associated with neurofascin 186 antibodies, thus expanding the potential spectrum of neurofascin 186-associated disease. This report supports the recommendation to consider also neurofascin 186 autoantibodies in not just peripheral nerve disease, but also in disorders involving CNS autoimmunity. More studies are needed to clarify the lack of association between neurofascin 186 autoantibodies and cognitive decline.